The Hybrid Cloud API Gateway Architecture with Zero Trust for Digital Banking - B. Junedi Hutagaol; Riama Santy Sitorus; Nadya Allia Putri (Puslitbang Sinergis Asa Professional, 2026)
The rapid adoption of digital banking services has increased the reliance on Application Programming Interfaces (APIs) to support integration, service delivery, and collaboration with external partners. However, the growing exposure of APIs has also introduced significant security risks, while financial institutions must simultaneously address scalability demands and regulatory compliance requirements. This study aims to design a Hybrid Cloud API Gateway Architecture integrated with Zero Trust Security principles for digital banking systems. The research employs a qualitative approach using the Design Science Research (DSR) methodology, consisting of literature review, requirements analysis, architecture design, expert validation, and architecture evaluation. The proposed architecture integrates API Gateway capabilities, Hybrid Cloud Architecture, and Zero Trust mechanisms to provide secure, scalable, and resilient banking services. Critical workloads and sensitive data are maintained within private cloud environments, while scalable services are deployed in the public cloud to improve flexibility and resource utilization. Evaluation results indicate that the proposed architecture aligns with NIST SP 800-207 Zero Trust Architecture principles, addresses major risks identified in the OWASP API Security Top 10, and supports compliance with PCI DSS and ISO/IEC 27001 standards. The proposed framework provides a practical reference for developing secure, scalable, and compliant digital banking infrastructures.